(untitled) (Medical Forum Monthly, 2024)
Objective: To look at the frequency of children having type 1 diabetes mellitus and their clinical profile. Study Design: Observational study Place and Duration of Study: This study was conducted at the Pediatric Ward, Peoples Medical College Hospital, Nawabshah from November 2016 to October 2017. Materials and Methods: Files of patients with either diagnosis at admission as diabetes mellitus type 1 or later diagnosed as diabetes mellitus type 1 during hospital stay were collected and data was retrieved regarding gender, age, number of days in hospital, presentation, type of insulin used, and acute complications developed if any. Results: Total patients admitted in ward 10554 from November 2016 to October 2017, age ranging from 1 year to 15 years. Out of these10554, 57 patients were treated as having type 1 diabetes mellitus, with a mean age of 7.5 years, the female were 61%. Mode of presentation was Diabetic ketoacidosis (DKA) in 50 patients, and 7 patients were diagnosed incidentally during stay at hospital for some other disease. 1 Patient developed cerebral edema during DKA management, 3 patients developed episodes of hypoglycemia, rest of the patients were discharged without complication. Conclusion: Diabetes mellitus type 1 in recent years has found to be an increased concern in pediatric population. In our patients it was found to be present in0.54% admitted patients. But there is a limitation of this study that it does not depicts the actual ice berg situation of this illness in our population